Immunization of suckling pigs against enterotoxigenic Escherichia coli-induced diarrheal disease by vaccinating dams with purified 987 or K99 pili: protection correlates with pilus homology of vaccine and challenge. - Morgan, R L (1978)
Pregnant gilts were vaccinated with purified strain 987 pili (987P), strain K99 pili, or a saline-formaldehyde control. Suckling pigs born to vaccinated gilts were allowed to consume colostrum and were then challenged intragastrically with one of three enterotoxigenic Escherichia coli strains: 987 (O9:K103, 987P:NM), 74-5208 (02O:K101, 987P:NM) or 431 (O101:K30, 99:NM). In litters where the dam was vaccinated with the same pilus as that possessed by the challenge organism, the incidence and duration of diarrhea and the degree of intestinal colonization (either duration or extent) were less than those of the other vaccine groups. Surviving pigs in the homologous vaccine groups also had better weight gains than pigs in the other vaccine groups. The experiments extend and confirm previous reports that vaccination of the dam with purified pili confers protection to neonatal suckling pigs against diarrheal disease caused by enterotoxigenic E. coli strains that possess the same pili. Protection did not extend to enterotoxigenic strains possessing different pili.